MAIN THREATS AFFECTING ARNICA MONTANA L. IN THE NORTHEASTERN REGION OF ROMANIAN CARPATHIANS - Constantin MARDARI; Ciprian Constantin BÎRSAN; Camelia Paula ŞTEFANACHE; Cătălin TĂNASE (Journal of Plant Development)
The current paper is focused on an emblematic medicinal species, Arnica montana, and on identification of the main threats it faces in the northeastern region of Romanian Carpathians. The species was investigated in 30 localities, in various habitats, characterized by different land management types, and different floristic composition of plant communities. The most important threat for A. montana in NE Carpathians was the habitat loss, mainly caused by abandonment of the traditional meadows management and natural succession of vegetation. Accumulated data underline the importance of management measures for A. montana, measures that have controlled and maintained the habitats of montane grasslands over time. The most suitable method of maintaining habitats in a favorable state of conservation could be represented by a combination of mowing and moderate intensity grazing while maintaining a level of fertilization as low as possible. Collection of flower heads for medicinal purposes must be avoided in small size populations.